Digitalization of the Logistics Industry – A Catalyst for Sustainable Economic Development in Vietnam - Phuong, Le Thi Nam; Phi, Pham Trinh Hong (International Journal of Research and Applied Technology (INJURATECH), 2024)
Logistics is an industry that supports, connects, and drives socio-economic development, enhancing competitiveness and generating high added value. However, in Vietnam, the imbalance between production and logistics in strategic planning and policy has led to challenges in sustainable development. In this discussion, we will examine the reasons, barriers, and methods for addressing these issues to achieve the sustainable development goals for the 2025-2030 period, with a visiontoward 2040.